PERAN KEPUASAN PELANGGAN MEMEDIASI PENGARUH CITRA MEREK TERHADAP NIAT BERPINDAH MEREK PELANGGAN GERAI KOPI STARBUCKS - Putra, Anak Agung Vedanta; Suprapti, Ni Wayan Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.06.TAHUN.2024, 2024)
Brand switching intention is the level of probability that a customer will switch from the current purchased or consumed product to another brand. This study aims to examine and explain the effect of brand image on brand switching intentions of Starbucks coffee shop’s customers in Denpasar City, and also to examine the mediating role of customer satisfaction. The data was taken from 110 sample customers purposively. The results of the study found that brand image had a positive and significant effect on customer satisfaction, brand image and customer satisfaction had a negative and significant effect on brand switching intentions, and customer satisfaction was able to mediate the effect of brand image on brand switching intentions. The implication of this research is a good brand image is an added value for a brand that can increase customer satisfaction, and able to cause less customer intention to switch brands. This research was conducted in Denpasar City with a relatively small sample size, so similar research is needed in other cities in Indonesia which have a fairly large number of Starbucks outlets.